2018
DOI: 10.1089/mdr.2017.0353
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Drug-Resistant Tuberculosis in Spain (2001–2015)

Abstract: Multidrug-resistant tuberculosis (MDR-TB) is a cause of increasing concern. This study investigated first-line anti-TB drug resistance in Mycobacterium tuberculosis strains submitted to the Tuberculosis Reference Center in Córdoba (Spain) between 2001 and 2015. A total of 1,207 cultures were tested against first-line drugs using the BACTEC MGIT 960 system. Resistance to first-line drugs was detected in 207 strains (17.2%), the greatest resistance being found in INH (5.3%) followed by streptomycin (3%), pyrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…İspanya'da 15 yıllık verilerle yapılan bir çalışmada 1,207 suşun 207'sinde (% 17.2) INH, RIF, SM ve ETM'den herhangi birine karşı direnç saptanmış, ilaçların her birine karşı toplam direnç oranları INH, RIF, SM ve ETM için sırasıyla % 5.3, % 1, % 3, % 0.2 olarak bulunmuştur (10) . Bu direnç oranları aynı yazarların önceki çalışmalarındaki direnç oranlarından daha düşük bulunmuştur.…”
Section: Discussionunclassified
“…İspanya'da 15 yıllık verilerle yapılan bir çalışmada 1,207 suşun 207'sinde (% 17.2) INH, RIF, SM ve ETM'den herhangi birine karşı direnç saptanmış, ilaçların her birine karşı toplam direnç oranları INH, RIF, SM ve ETM için sırasıyla % 5.3, % 1, % 3, % 0.2 olarak bulunmuştur (10) . Bu direnç oranları aynı yazarların önceki çalışmalarındaki direnç oranlarından daha düşük bulunmuştur.…”
Section: Discussionunclassified
“…in Spain, but the few that exist offer much lower data than those estimated by the WHO, estimating that MDR/MDR-TB would be around 1% of new TB cases [77,78,79], or around 40-60 cases per year.…”
Section: What Is the Resistance To Anti-tuberculosis Drugs In Europe ...mentioning
confidence: 92%
“…These figures are very similar to those estimated at the global level worldwide [ 76 ], although in Spain there seems to be a clear difference between the autochthonous population with low rates of MDR/MDR-TB and patients born outside our country, with clearly higher figures [ 77 ]. Unfortunately, there are hardly any publications addressing this issue in Spain, but the few that exist offer much lower data than those estimated by the WHO, estimating that MDR/MDR-TB would be around 1% of new TB cases [ 77 , 78 , 79 ], or around 40-60 cases per year.…”
Section: What Is the Resistance To Anti-tuberculosis Drugs In Europe ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study consisting of 26,228 patients from Germany, resistance rates were reported as 7% for streptomycin, 7% for isoniazid, and 2% for rifampicin (7). Resistance rates in Spain between 2001 and 2015 were 5.3% for isoniazid, 1% for rifampicin, 3% for streptomycin, and 0.2% for ethambutol (8). Of the 316 M. tuberculosis isolates in Kosovo, resistance to isoniazid, rifampicin, ethambutol, and streptomycin was seen in 8%, 3%, 17% and 72% of isolates, respectively (9).…”
mentioning
confidence: 99%